Electronic structure of mono(Lewis base)-stabilized borylenes. Issue 42 (16th October 2019) - Lu, Dongmei; He, Yijin; Wu, Chao
Abstract : Mono(Lewis base)-stabilized 3c-6e borylenes are found to have multiple ground state electronic structures. Abstract : This work demonstrates that the mono(Lewis base)-stabilized three-center-six-electron (3c-6e ) or LB → B–R type borylenes may have a ground state singlet (σ 2 π 0 and σ 0 π 2 ) or triplet (σ 1 π 1 ) electronic structure, depending on the substitution group, Lewis base, and molecule topology (cyclic or acyclic). The singlet–triplet energy gap of a borylene increases with electron-donating substitution groups and decreases with Lewis bases of strong σ-donating and π-accepting feature ( e.g., carbenes and pyridine). The gap can be widely varied (ranging up to about 300 kJ mol −1 ) and even inversed by the proper combination of substitution groups and Lewis bases. These borylenes may even have singlet-and-triplet coexisting ground state electronic structures, which imply their complex reactivity.